Predicting In-Hospital Treatment Failure (≤7 days) in Patients with COPD Exacerbation Using Antibiotics and Systemic Steroids. (2nd January 2016) - Crisafulli, Ernesto; Torres, Antoni; Huerta, Arturo; Guerrero, Mónica; Gabarrús, Albert; Gimeno, Alexandra; Martinez, Raquel; Soler, Néstor; Fernández, Laia; Wedzicha, Jadwiga A.; Menéndez, Rosario
Abstract: Although pharmacological treatment of COPD exacerbation (COPDE) includes antibiotics and systemic steroids, a proportion of patients show worsening of symptoms during hospitalization that characterize treatment failure. The aim of our study was to determine in-hospital predictors of treatment failure (≤ 7 days). Prospective data on 110 hospitalized COPDE patients, all treated with antibiotics and systemic steroids, were collected; on the seventh day of hospitalization, patients were divided into treatment failure (n = 16) or success (n = 94). Measures of inflammatory serum biomarkers were recorded at admission and at day 3; data on clinical, laboratory, microbiological, and severity, as well data on mortality and readmission, were also recorded. Patients with treatment failure had a worse lung function, with higher serum levels of C-reactive protein (CRP), procalcitonin (PCT), tumour necrosis factor-alpha (TNF-α), interleukin (IL) 8, and IL-10 at admission, and CRP and IL-8 at day 3. Longer length of hospital stay and duration of antibiotic therapy, higher total doses of steroids and prevalence of deaths and readmitted were found in the treatment failure group. In the multivariate analysis, +1 mg/dL of CRP at admission (OR, 1.07; 95% CI, 1.01 to 1.13) and use of penicillins or cephalosporins (OR, 5.63; 95% CI, 1.26 to 25.07) were independent variables increasing risk of treatment failure, whereas cough at admission (OR, 0.20; 95% CI, 0.05 to 0.75) reduces risk of failure. In hospitalized COPDE patients CRP at admission and use of specific class of antibiotics predict in-hospital treatment failure, while presence of cough has a protective role.